The experiences and perceived health benefits of individuals with a disability participating in sport: A systematic review and narrative synthesis. Issue 1 (January 2022) - Aitchison, Beth; Rushton, Alison B.; Martin, Paul; Barr, Marc; Soundy, Andrew; Heneghan, Nicola R.
Abstract: Background: Sports participation has many physical and mental health benefits for individuals with a disability including improved functionality and reduced anxiety, yet a large proportion of individuals with a disability are inactive. Objective: To investigate the experiences and perceived health benefits of sport participation across four disability populations: children and adolescents, adults, elite athletes and veterans with a disability. Methods: A mixed-methods systematic review was conducted. Eligible studies had participants who were children, adults, elite athletes or veterans with a physical, visual or intellectual disability. Data were extracted using the Joanna Briggs Institute (JBI) tool and quality assessment involved the Quality Assessment Tool for Studies with Diverse Designs (QATSDD). Content, thematic and narrative synthesis techniques were used. Confidence in cumulative evidence was determined using GRADE-CERQual and Classes of Evidence. Results: Several positive aspects of sport participation were highlighted across all four populations, including socialisation opportunities, pure enjoyment, a sense of freedom and providing an arena to challenge stereotypes. The paucity of research within the 'veterans with a disability' group limited analysis of experiences and benefits of sport in this population. Conclusions: This systematic review was the first to explore this phenomena, finding that overall sport is a beneficial experience for individuals with a disability. The positive aspects should be promoted when encouraging sport participation for children, adolescents, adults and elite athletes. More research is needed to explore these phenomena in veterans and to compare perceived benefits between populations to enable tailored promotion of sport.